2022
DOI: 10.21203/rs.3.rs-2164442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RPL22L1, a Novel Candidate Oncogene Promotes Temozolomide Resistance by Activating STAT3 in Glioblastoma

Abstract: Aggressiveness and drug resistant are major challenges in the clinical treatment of glioblastoma (GBM). Our previously research reported a novel candidate oncogene ribosomal protein L22 like 1 (RPL22L1). The aim of this study was to elucidate the potential role and mechanism of RPL22L1 in progression and temozolomide (TMZ) resistance of GBM. Online database, tissue microarrays and clinical tissue specimens were used to evaluate the expression and clinical implication of RPL22L1 in GBM. We performed cell functi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Chen et al found that RPL22L1 promoted glioblastoma resistance to temozolomide by activating STAT3 pathway. [10] Zhang et al demonstrated that RPL22L1 contributed to sorafenib resistance in hepatocellular carcinoma through the ERK signaling pathway. [11] In addition, a study by Rao indicated that RPL22L1 was associated with poor prognosis and 5-FU resistance in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al found that RPL22L1 promoted glioblastoma resistance to temozolomide by activating STAT3 pathway. [10] Zhang et al demonstrated that RPL22L1 contributed to sorafenib resistance in hepatocellular carcinoma through the ERK signaling pathway. [11] In addition, a study by Rao indicated that RPL22L1 was associated with poor prognosis and 5-FU resistance in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%